Sustainable Construction Practices: A Green Transformational Leadership Perspective - Jatmiko Murdiono; Hamidah Hamidah; Tuty Sariwulan; Dewi Susita; Siti Hafsah Zulkarnain (Dinasti International Journal of Education Management And Social Science, 2025)
With the growing awareness of climate change?and environmental degradation, sustainable construction practices have become more relevant than ever. Therefore, green leadership is one of the approaches known to promote sustainability in the construction industry. This paper investigates the implementation of green leadership in sustainable construction, focusing on its significance, challenges, strategies, and advantages. This paper also aims to map green transformational leadership in construction as a guide for industry?players by examining the interaction between a sustainable leadership style and the competencies of sustainable construction practices. It is concluded from this analysis that specific competencies and styles of leadership that are goal-oriented, involving, and?engaging will determine construction project sustainability and effectiveness. Thus, construction executives should embed sustainability into the purpose, strategy, and operation of their?businesses. In addition, the acquisition of green leadership skills and sustainability drives organizations toward a sustainable future for ?construction practices.